Towards sustainable fats, oils and greases (FOG) management: from waste to resource. - Collin, Thomas Denis (Cranfield University, 2019)
Fats, oils and greases (FOG) are by-products of cooking and food preparation originating from households, food service establishments (FSEs) and industrial food facilities. Under UK legislation, industries are the only sources of FOG monitored by water authorities under trade effluent consents. In addition, whilst all FSE kitchens must be fitted with an “effective mean of grease removal”, experience within the water sector has demonstrated that very few premises were managing their effluents to minimise FOG emissions. Critically, large volumes of FOG are entering drainage systems resulting in impacts both in the sewers (formation of fatbergs) and downstream at the treatment works (reduced treatment efficiency), and in turn contributing to high operational costs for water utilities. With changing food habits and projected population growth, FOG-related problems will only become an increasingly worrying operational and financial burden for the water industry. Yet, FOG can be a valuable resource for energy recovery with the potential to offset operational costs and improve the overall sustainability of wastewater treatment. This thesis establishes an evidence base by assessing the potential of alternative FOG management options in order to provide guidance to water utilities for improving current practices. A comprehensive study identified the contribution of current kitchen practices to FOG emissions from domestic and commercial sources, suggesting the need for educational campaigns to raise awareness on the problem. Production rates and quality of FOG from different sources were benchmarked clarifying variations amongst these wastes. The potential of FOG for energy recovery, via biogas generation from anaerobic digestion, was assessed through laboratory-scale studies. The occurrence of FOG at the treatment works was investigated, and the performance of enhanced treatment for its removal was further studied. Finally, data produced during this project was used to develop a business case for the implementation of more sustainable approaches.
Keywords: Anaerobic digestion; fatberg; sewer deposits; sewage treatment works (STW); dissolved air floatation (DAF); grease separator